ALTERNATIVE ENERGY SOURCEFOR AUTOMOBILE VEHICLE - Gore Samrat S.; Shete Abhijit C.; Kadnor Ganesh S.; Sonwane Swapnil N. (International Journal of Innovations in Engineering Research and Technology, 2021)
Alternate energy source of magnetic levitation propulsion used in automobile, with self-generation of electricity for charging the battery. This is a four wheel vehicle with drive mechanism being propelled by the magnetic levitation which is used in maglev trains. Here the piston is moving within the coil to effect the to and fro motion when energized, to effect the cranking and rotations which drives the vehicle. The control circuit is provided for giving the acceleration, the batteries are provided for the control circuit and the battery meant for energizing the coils is to be arranged externally.